2018
DOI: 10.3390/ma11040499
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effect of Hydrogen on Fracture Toughness of 2.25Cr-1Mo-0.25V Steel and Welds after Annealing

Abstract: Hydrogen embrittlement (HE) is a critical issue that hinders the reliability of hydrogenation reactors. Hence, it is of great significance to investigate the effect of hydrogen on fracture toughness of 2.25Cr-1Mo-0.25V steel and weld. In this work, the fracture behavior of 2.25Cr-1Mo-0.25V steel and welds was studied by three-point bending tests under hydrogen-free and hydrogen-charged conditions. The immersion charging method was employed to pre-charge hydrogen inside specimen and the fracture toughness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Nonetheless, to our knowledge, influence of pre-charged hydrogen on fracture toughness of 2.25Cr1Mo0.25V welded joint has rarely been investigated. In our previous article [ 9 ], the influence of pre-charged hydrogen on the 2.25Cr1Mo0.25V steel and weld after post weld heat treatment (PWHT, i.e., Annealing) was studied. However, due to the influence of the PWHT, the reduction of fracture toughness caused by pre-charged hydrogen was limited, thus, it’s hard to clarify the intrinsic effect of pre-charged hydrogen on fracture toughness of 2.25Cr1Mo0.25V steel and weld.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, to our knowledge, influence of pre-charged hydrogen on fracture toughness of 2.25Cr1Mo0.25V welded joint has rarely been investigated. In our previous article [ 9 ], the influence of pre-charged hydrogen on the 2.25Cr1Mo0.25V steel and weld after post weld heat treatment (PWHT, i.e., Annealing) was studied. However, due to the influence of the PWHT, the reduction of fracture toughness caused by pre-charged hydrogen was limited, thus, it’s hard to clarify the intrinsic effect of pre-charged hydrogen on fracture toughness of 2.25Cr1Mo0.25V steel and weld.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of HE susceptibility of materials can be quantified by measuring different parameters, such as reduction in area, fatigue crack-growth rate, fatigue life, fracture toughness, and time to failure [31,50]. Reduction in the tensile strength and elongation suggests that the base metal samples and the HAZ samples of X80 steel were strongly susceptible to HE [3,51], as shown in Figure 5, with a general trend that the HE susceptibility increases with an increase in the hydrogen concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of welding thermal cycles on the microstructure has attracted more attention, since welding is widely used to construct long-distance pipeline steel [28,29]. Microstructure heterogeneity are affected by welding thermal cycle processes, which change the hydrogen diffusion and accumulation [30,31]. Thus, there is a great difference between the base metal and heat-affected zone (HAZ) tested in the hydrogen environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydrogen can be inserted into the steel during the manufacturing and operating processes. This may lead to the degradation of the mechanical properties of the 2.25Cr-1Mo-0.25V steel, (i.e., hydrogen embrittlement (HE) [1,2]), and may also lead to hydrogen-induced cracking (HIC) [3,4] during the operating process. These will gravely affect the reliability of the reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia et al [1] analyzed the effect of HE on the tensile properties of three different grades of CrMoV steel by the small punch experiment, indicating that CrMoV steel has a high susceptibility to HE, and the tensile properties are relative to the different grades of the CrMoV steel. Song et al [2] studied the effect of HE on the fracture toughness of 2.25Cr-1Mo-0.25V steel and the welds after annealing by a three-point bending experiment and found that the fracture toughness for the steel and welds significantly decrease under hydrogen-charged conditions, and the steel shows a superior resistance to HE than the welds. Meanwhile, there are two mechanisms for HE in metallic materials: (i) hydrogen-enhanced decohesion model (HEDE) [5,6], (ii) hydrogen-enhanced localized plasticity model (HELP) [7].…”
Section: Introductionmentioning
confidence: 99%